The interplay between airway epithelium and the immune system – A primer for the respiratory clinician. (June 2021) - Weinstock, Jered; Chen, Xilei Xu; Nino, Gustavo; Koumbourlis, Anastassios; Rastogi, Deepa
Abstract: The respiratory epithelium is one of the primary interfaces between the body's immune system and the external environment. This review discusses the innate and adaptive immunomodulatory effects of the respiratory epithelium, highlighting the physiologic immune responses associated with health and the disease-causing sequelae when these physiologic responses go awry. Airway macrophages, dendritic cells, and innate lymphoid cells are discussed as orchestrators of physiological and pathological innate immune responses and T cells, B cells, mast cells, and granulocytes (eosinophils and neutrophils) as orchestrators of physiologic and pathologic adaptive immune responses. The interplay between the airway epithelium and the varied immune cells as well as the interplay between these immune cells is discussed, highlighting the importance of the dose of noxious stimuli and pathogens in immune programming and the timing of their interaction with the immune cells that determine the pattern of immune responses. Although each cell type has been researched individually, this review highlights the need for simultaneous temporal investigation of immune responses from these varied cells to noxious stimuli and pathogens.